Conducting research surveys via e-mail and the web - Schonlau, Matthias, 1967- (Rand, 2002)
Internet-based surveys, although still in their infancy, are becoming increasingly popular because they are believed to be faster, better, cheaper and easier to conduct than surveys using traditional methods. This text examines the pros and cons of Internet-based surveys.